2014
DOI: 10.1038/ncb2951
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: MicroRNA-146a directs the symmetric division of Snail-dominant colorectal cancer stem cells

Abstract: In the version of this Article originally published, the labels of the key in the upper panel of Fig. 7h should have read 'HT29-Vec' (black) and 'HT29-146a' (grey). This error has now been corrected in the online versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Additionally, microRNAs associated with self-renewal and differentiation play a relevant role in cancer. They generally sustain activation of the Notch/Wnt signaling pathway or suppress the expression of differentiation-related transcription factors (Bu et al 2013a ; Hwang et al 2014 ; Mukherjee et al 2015 ). Furthermore, defects in AKT, TP53, and EGFR signaling can disrupt the balance between asymmetry and symmetry, leading to neoplastic transformation (Bu et al 2013b ; Mukherjee et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, microRNAs associated with self-renewal and differentiation play a relevant role in cancer. They generally sustain activation of the Notch/Wnt signaling pathway or suppress the expression of differentiation-related transcription factors (Bu et al 2013a ; Hwang et al 2014 ; Mukherjee et al 2015 ). Furthermore, defects in AKT, TP53, and EGFR signaling can disrupt the balance between asymmetry and symmetry, leading to neoplastic transformation (Bu et al 2013b ; Mukherjee et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, long non-coding RNA, Lnc34a, is enriched in colon cancer stem cells and initiates asymmetric division by directly targeting the microRNA miR-34a to cause its spatial imbalance (Wang et al 2016 ). In other studies, miR-146a was found to activate WNT signaling and induce a switch from asymmetric to symmetrical division by targeting Numb in spheroid-derived colorectal cancer stem cells (Hwang et al 2014 ). In breast cancer, The Myc signaling pathway is essential for stem cell maintenance and is predominantly expressed in stem cells, not in differentiated cells, during asymmetric cell division.…”
Section: Asymmetric Division In Cancer Initiationmentioning
confidence: 93%
See 1 more Smart Citation